Quality of Business Partners in Marketing Rembangan Dairy Farm's Pure Milk in Maintaining Quality - Qodariyah, Niyar Ana; Wardani, Diana Widyaningtyas; Mudakir, Imam; Asyiah, Iis Nur (Jurnal Biologi Tropis, 2024)
Rembangan Dairy Farm, which is located at UPT Livestock Breeding and HPT Rembangan WM8R+734, Darungan, Kemuning Lor, Kec. Arjasa, Jember Regency, East Java, is a cow's milk processing industrial area. The purpose of this study is to find out how the agro-industry forms in Rembangan Dairy Farm. The research method applied in this study is qualitative research with a case study approach. Data collection techniques through observation, interviews and documentation. Data analysis uses descriptive analysis according to the facts found in the field. The results of this research are that the milk processing process in industry still uses a simple method, namely the pasturization stage. The dairy products produced consist of two types, namely pure fresh milk without any additions and fresh milk with a variety of flavors. Milk marketing techniques are carried out online via social media Instagram and Whatsapp, and also offline through milk outlets and business partners. Marketing of fresh milk by business partners needs to be further improved in maintaining the durability of milk using refrigerators or freezers, this is because fresh milk is susceptible to temperature so it can easily spoil if not stored in the correct way. There is a need for further education for business partners to be able to maintain product quality by storing it properly so that the products being marketed do not suffer damage when in the hands of consumers.